Active Compounds In The Aqueous Extract Of Ludwigia Octovalvis Leaves As Antibacterial Agents Against Pathogens - Siti Aminah; Siti Aisiah; Fatmawati (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Ludwigia octovalvis is a tropical aquatic weed with potential as a medicinal plant due to its diverse secondary metabolite content. This study aimed to quantify the secondary metabolite profile of aqueous extracts of Ludwigia octovalvis leaves and evaluate their potential as natural antibacterial agents. Leaves were collected from wetlands in Tungkaran Village, Martapura, Banjar Regency, South Kalimantan, and extracted using distilled water at a ratio of 1:4. Quantitative phytochemical analysis was performed in triplicate for saponins, alkaloids, flavonoids, terpenoids, tannins, steroids, anthocyanins, and phenolics. Ludwigia octovalvis leaf extract contains secondary metabolite compounds, namely saponins (15.587%), alkaloids (6.507), flavonoids (91.667 mg/g), terpenoids (228.467 mg/g), tannins (0.850 mg/g), steroids (39.177 mg/g), anthocyanins (negative), and phenolics (65.467 mg/g). The highest levels of secondary metabolites are found in terpenoid compounds, namely 228.467 mg/g and the lowest in negative anthocyanin compounds. These secondary metabolite compounds have the potential as antibacterials against Aeromonas hydrophila bacteria.